PENGARUH INKLUSI DAN LITERASI KEUANGAN TERHADAP KINERJA USAHA DENGAN KEBERLANJUTAN USAHA SEBAGAI VARIABEL INTERVENING PADA SEKTOR USAHA UMKM DI KOTA DEPOK - Finatariani, Endah; Rosini, Iin; Nofriyanti, Nofriyanti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
In Depok City, the MSME (Micro, Small and Medium Enterprises) business sector plays an important role in the local economy. However, most MSMEs in the city still face various challenges, including financial access issues and low financial literacy levels. Therefore, financial inclusion and financial literacy have the potential to have a positive impact on the business performance of MSMEs in Depok City. This study aims to test and analyze the effect of financial inclusion and financial literacy with business sustainability as an intervening variable in the MSME business sector in Depok City. This study involved MSME players in Depok City using the Non Probability sampling method with a population of 7911 which was processed using the Slovin formula into 100 research samples. The data were processed using the Partial Least Square- Structural Equation Modeling (PLS-SEM) method. This type of research is quantitative research, using primary data, the findings report that Financial Inclusion affects the Performance and Sustainability of MSME Businesses, Financial Literacy affects the Performance and Sustainability of MSME Businesses, as evidenced by Business Sustainability being able to mediate Financial Inclusion on MSME Performance and Business Sustainability being able to mediate Financial Literacy on MSME Performance. This can be a reference for MSME players to realize the importance of access to banking services to get the best results. finance so that it can improve the performance of MSMEs and their Business Sustainability. Based on the results of this study, many MSMEs continue to survive in their business activities, it is proven that they are able to survive for more than 5 years in Depok City.